Tonal languages as ethnomathematical objects for strengthening graphical representation literacy and advanced mathematical thinking - Andri Suryana; Yulian Dinihari; Mohamed Aidil Subhan (CV. FOUNDAE, 2026)
Background: Advanced Mathematical Thinking, AMT, is crucial in higher mathematics education, yet many students struggle to read and interpret graphical representations, indicating weak representational literacy. Ethnomathematics offers a culturally grounded bridge between abstract mathematics and meaningful real-world phenomena. Aims: This study aims to explore tonal language pitch as an ethnomathematical object that can be used to strengthen literacy in reading representations and support the development of Advanced Mathematical Thinking, AMT, among mathematics education students. Method: An exploratory qualitative approach with a mini-ethnographic design was used. Data were collected through recordings of native speakers of Thai, Mandarin, and Vietnamese, visualizations of frequency–time curves, and students’ activities in interpreting graphs. Results: Acoustic analysis shows that the pitch contours of the three tonal languages have consistent patterns and can be modeled as constant, linear, quadratic, or sinusoidal functions. The findings indicate that the activity of reading pitch curves helps students understand patterns of change, gradients, extreme points, and relationships between variables more intuitively. Conclusion: Pitch curves derived from cultural phenomena make mathematical graphs more contextual and easier to interpret, thereby strengthening literacy in reading visual representations. In addition, this activity promotes the development of AMT aspects such as structural awareness, the ability to generalize patterns, and making connections.